Banana improvement : (Science Publishers, 2004)
The book is based on the research and development of tools, devised under a Coordinated Research Project of the Plant Breeding and Genetics Section of the Joint Division FAO/IAEA, to address the problems facing banana and plantain cultivation. The book comprises 30 chapters by the experts and renowned scientists. The work is divided into four sections.